Analytic hierarchy process for urban transportation: a bibliometric and social network analysis - Kenger, Zuelal Diri; Kenger, Omer Nedim; Ozceylan, Eren (SPRINGER)
Increasing population and urbanization create many problems, especially traffic problems in urban areas. Public transportation is becoming a necessity since it is seen as a solution for traffic problems. This paper conducts bibliometric and social network analysis on urban and public transportation literature that use Analytic Hierarchy Process (AHP) technique. In this study, 222 papers were reviewed. These papers were published between 1987 and 2022 and were extracted from the Web of Science database. Analyses are realized in order to identify trends, and key points in a more scientific and objective way. Analysis results show that there is great increase in number of publications in the last 10 years. Most active author according to publication number is Duleba S., the journal that has the most publications is "Sustainability", and most productive country is China. Hybrid methodologies such as AHP-TOPSIS and Fuzzy AHP also are frequently used in publications. Furthermore, the AHP technique has been frequently used for measuring service quality, bus selection, vehicle selection, determination of facility location, passenger satisfaction, and bus-bicycle routes. To achieve sustainable urban transportation, it is crucial to adopt smart and eco-friendly technological solutions that cater to the diverse needs of current and potential users. Integrating various transportation modes is also essential for ensuring safety and sustainability of urban transportation systems. Furthermore, public transportation vehicles based on clean technology should be prioritized over other options since they promote cleaner air in cities, particularly in densely populated areas, leading to better air quality and more livable cities.
Keywords: Literature review; Social network analysis; Bibliometric; Public transport; Analytic hierarchy process